Optimization modeling with spreadsheets - Baker, Kenneth R., 1943- (Hoboken : Wiley, 2016)
'Thoroughly updated to reflect the latest topical and technical advances in the field, Optimization Modeling with Spreadsheets, Third Edition continues to focus on solving real-world optimization problems through the creation of mathematical models and the use of spreadsheets for analysis. Developed and extensively classroom-tested, the book features a systematic approach that equips readers with the skills needed to apply optimization tools effectively without the need to rely on specialized algorithms. This introductory book on optimization (mathematical programming) includes coverage on linear programming, nonlinear programming, integer programming, and heuristic programming, with an emphasis on model building using Excel's freely available Solver. The focus on model building (rather than algorithms) is one feature that makes this book distinctive as most books devote more space to algorithmic details than to formulation principles. These days, however, it is not necessary to know a great deal about algorithms in order to apply optimization tools, especially when relying on the spreadsheet as a solution platform. This emphasis on spreadsheets is another feature that makes this book distinctive. Few books devoted to optimization pay much attention to spreadsheet implementation of optimization principles, and most books that emphasize model building ignore spreadsheets entirely. To address the capabilities of sensitivity analysis, the use of Excel's Sensitivity Toolkit is employed. In addition, the book's past use of the Risk Solver Platform for Education (RSPE) is not completely abandoned as the author does include instructions on the use of RSPE for solving optimization problems within an appendix'--
'This book focuses on solving real-world optimization problems through the creation of mathematical models and the use of spreadsheets for analysis. Developed and extensively classroom-tested, the book features a systematic approach that equips readers with the skills needed to apply optimization tools effectively without the need to rely on specialized algorithms. This introductory book on optimization (mathematical programming) includes coverage on linear programming, nonlinear programming, integer programming, and heuristic programming, with an emphasis on model building using Excel's freely available Solver'--
Revised edition of the author's Optimization modeling with spreadsheets, 2011.
Includes bibliographical references and index.
Keywords: Mathematical optimization; Managerial economics -- Mathematical models; Electronic spreadsheets; Programming (Mathematics); BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Project Management; TECHNOLOGY & ENGINEERING / Industrial Engineering